EXPLORING CRITICAL SKILLS ELEMENTS IN MALAYSIA'S ELECTRONICS INDUSTRY - Norhamimi Hamdan; Asnul Dahar Minghat; Fatimah Salim, (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2024)
This study aims to explore Critical Skills Elements in Malaysia's Electronics Industry. An investigation was conducted to identify the skills requirement and insufficient critical skills among fresh graduates for entering the job market, as well as its impact on productivity and the success of company operations. Through interviews with five participants consisting of managers and company executives in the electronic engineering industry, several key themes were identified. The findings show the importance of technical skills, communication ability, problem-solving ability, and adaptation to new technology. This lack of skills is identified as the main reason for the decrease in productivity and disruption in company operations. Recommendations to educational institutions were also discussed to ensure that the curriculum offered aligns with current industry needs. As a result of the study, an academic model was formed to solve this problem, concentrating on closer integration between educational institutions and industry. This study contributes to a deeper understanding of the skills gap between graduates and industry needs, as well as providing practical recommendations to strengthen the fit of the engineering education curriculum with the demands of the job market.